Analysis of traffic-induced vibrations by blind source separation with application in building monitoring - Popescu, Th.D. (Mathematics and computers in simulation, 2010)
The paper presents an approach that may enable the separation of the vibrations induced by underground traffic from the vibrations induced by other sources, based on Second Order Blind Identification (SOBI) algorithm. The signals recorded in different locations of an instrumented building are mixed signals from different internal and external vibration sources. The blind source separation algorithm will estimate the independent vibration sources together with their mixing model. This model can be used to determine the contribution of each source in different measurement points, to evaluate the effect of the vibration sources and their potential for building damage. The above approach has been tested in simulation and on a building subject to different traffic forms.